Design of Temperature Monitoring and Stabilization System Based on Microcontroller for Outdoor Jacket in Cold Regions - Thabliq Basac Bhaskara; Muhammad Daud; Selamat Meliala (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The design of a temperature monitoring and stabilization system on a microcontroller based cold region outdoor jacket by utilizing microcontroller technology, by ensuring user comfort while in a cold temperature environment. This research is shown specifically in cold areas, with the aim of preventing hypothermia commonly experienced by climbers or humans, who are active in cold areas. The results of the system research on outdoor jackets that can monitor and stabilize the user's body temperature automatically, especially in cold areas. This system uses an ESP32 microcontroller, which is equipped with the Blynk application to control and monitor temperature using a smartphone. When the ambient temperature drops below 20°C, the system automatically activates the carbon fiber heating pad to maintain a stable body temperature. The jacket is designed to function offline, where the system will rely on the temperature sensor to activate the carbon fibre heating pad if the temperature drops below 20°C. Test results show that the system works well, providing efficient results in power consumption, responsive to temperature changes, and effective in maintaining temperature stability. The resulting jacket is comfortable and safe so that it does not interfere with outdoor jacket users in various conditions.